Seasonal cycle of the mixed layer, the seasonal thermocline and the upper-ocean heat storage rate in the Mediterranean Sea derived from observations. (March 2015) - Houpert, L.; Testor, P.; Durrieu de Madron, X.; Somot, S.; D'Ortenzio, F.; Estournel, C.; Lavigne, H.
Highlights: First climatology of the seasonal thermocline slope in the Mediterranean Sea. First climatology of the upper-ocean heat storage rate in the Mediterranean Sea. Implication of sub-basin circulation patterns in the ocean heat storage. Updated climatology of the mixed layer depth and temperature in the Mediterranean Sea. Abstract: We present a Mediterranean climatology (1° × 1° × 12 months) of the mixed layer and of the seasonal thermocline, based on a comprehensive collection of temperature profiles spanning 44 years (1969–2012). The database includes more than 190, 000 profiles, merging CTD, MBT/XBT, profiling floats, and gliders observations. This data set is first used to describe the seasonal cycle of the mixed layer depth and temperature, together with the seasonal thermocline depth and averaged temperature, on the whole Mediterranean on a monthly climatological basis. Our analysis discriminates several regions with coherent behaviors, in particular the deep water formation sites, characterized by significant differences in the winter mixing intensity. Heat Storage Rate (HSR) is calculated as the time rate of change of the heat content due to variations in the temperature integrated from the surface down to the base of the seasonal thermocline. For the first time the quantification of heat storage rate in the upper-ocean, based only on in situ oceanographic data, is made for the whole Mediterranean. The spatial and temporal variability of the HSR in the Mediterranean Sea and its link with dynamic structures like oceanic gyres are also discussed.